(untitled) (Itinera, 2024)
Since the early 2000s, computational informatics has increasingly entered the artistic sphere, traditionally a human monopoly. Generative artificial intelligences follow creative processes that are seemingly similar to human ones: they learn from existing works, grasp stylistic canons, and ultimately generate a new artifact that is aesthetically pleasing. Some of them have passed the Turing test, which may lead to the claim that we have reached a point where machines are capable of thinking, feeling, and knowing, thus undermining human beings from their domain in art and all creative fields. However, this perspective of exalting computational creativity has several critical points that can be refuted through contributions from fields such as philosophy and neuroscience. Art and culture have a symbolic value that cannot be generated by computational processes: they help define the Umwelt through which humans experience the world; they reflect the worldview of an era and a society; they attribute meanings to existence and reality. Therefore, it is challenging to summarize a work of art through computational models, as it contains a dimension of meaning that goes beyond form and cannot be exhausted through the logic of language, words, or computer signs. Finally, creativity is a much more complex process than simple learning and reshuffling of data: it is an ontological characteristic of human beings and is the result of millennia of evolutionary processes, which have led humans to develop conscious minds that - through a complex relationship between sensory perception, neural networks, and emotions - enable reasoning and creative thinking. The case of musical composition illustrates the gap between human creativity and artificial creativity: computational algorithms are to be seen as new mediums that open up new expressive possibilities for artists, but they cannot completely replace the human element in the creative process.